PENGARUH KOMPETENSI APARATUR, PARTISIPASI MASYARAKAT, PEMANFAATAN TEKNOLOGI INFORMASI, DAN KOMITMEN ORGANISASI PEMERINTAH DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (Studi Empiris di Desa Simandraolo dan Desa Hilinamazihono Kabupaten Nias Selatan) - Vinsensia Ratna Laia; Arthur Simanjuntak; Tri Darma Sipayung (JURNAL MANAJEMEN, 2022)
This study aims to determine the effect of apparatus competence, community participation, use of information technology, and village government organizational commitment to the accountability of Village Fund management in Simandraolo Village and Hilinamazihono Village. This type of research is quantitative with a causal associative approach. This research was conducted in Simandraolo and Hilinamazihono villages in South Nias Regency. The population and sample in this study were 31 people where in Simandraolo village there were 14 people and Hilinamazihono village were 17 people. This study uses primary data obtained by using a questionnaire. While the data analysis method used in this study is multiple linear regression analysis method which was carried out with the help of SPSS 25 software. The results of this study indicate that the Apparatus Competence and Organizational Commitment of the Village Government have a positive and significant influence on the accountability of village fund management while Community Participation and Utilization information technology has no influence on the accountability of village fund management. However, it can be seen that simultaneously all independent variables in this study have a significant influence on the Accountability of Village Fund Management.Â